Very High Frequency Distilled Water Antenna - Zulkifli, Muhammad Anwar (Universiti Sains Malaysia, 2018)
This research is focused on the study of water antennas, a type special type of liquid antenna that has drawn a lot of attentions recently. The water antenna utilized distilled water as the medium and operate within the VHF band. The proposed distilled water antenna can be an alternative to traditional antenna for many applications especially in a military field, marine communication system, and aircraft short range communication. The main objective of this research is to design, fabricate and test a VHF distilled water antenna. The container of the water antenna is made up from a PVC material. Two different diameters of PVC tubes are used in the experiment. The specifications of the PVC tubes are; height = 150 cm, thickness = 0.2 cm, diameter = 2.54 cm (1-inch) and 5.08 cm (2-inch). An aluminium plate with a dimension of 34 cm x 43 cm is used as the ground plane. A 1 m brass rod is permanently placed inside the PVC tube. The performance of the antenna is determined in terms of resonant frequency, return loss, bandwidth, gain and the radiation pattern. The height of water level is adjusted within the range of 0.25-1.5 m with a 0.25 m gap each. Both 1-inch and 2-inch water antenna showed a decrease in terms of resonant frequency when the water level is increased. The antenna also resonated within the VHF range for each water level. It is also observed that the volume of water affects the resonant frequency of the water antenna. The return losses measured are all below -10 dB and the recorded bandwidth are around 8 -20 MHz. Both gain and radiation pattern are measured using a frequency of 85.362 MHz. Two monopole antennas are used as the reference antenna during the measurement of gain. After calculation, the gain of the water antenna has been identified with a value of 1.915 dB. The water antenna also has the wider bandwidth and a better return loss compared to the reference monopole antenna. For the analysis of radiation pattern, the 1-inch water antenna has the highest received power of -17.82 dBm at 280˚ using 0.25 m distilled water. While for 2-inch water antenna, the highest received power is -17.17 dBm at 20˚ using 0.5 m distilled water. Overall, it can be concluded that the VHF distilled water antenna shows a good performance with high resonant frequency, good return loss and a wide bandwidth.